Educational Game “Mr. Foodi" Healthy and Nutritious Food for Children - Fadila Tiara; Reza Andrea; Suswanto (TEPIAN, 2021)
Children really like food that makes them interested in trying it, but the food that makes them interested is likely to be one of them. Source of problems for his health. Food and drinks that do not know the manufacturing process have an impact on children's development. Therefore, an educational game was created to get to know healthy and nutritious food. This is so that children can know which food is good for them and which food is not good for consumption. In its implementation, game development can use Construct2. Construct2 is a device that is used specifically for making games for platforms 2D. Games that use construct2 can be applied to educational games about healthy and nutritious food using the method finite state machine. FSM is a game smart agent development in the field of artificial intelligence. Methods Finite state machine (FSM) is a control system design methodology that describes the behavior or the working principle of the system by using the three things, namely, state, event and action.